PENERAPAN DAKWAAN ALTERNATIF TERHADAP PELAKU PENYERTAAN TINDAK PENIPUAN ONLINE(STUDI KASUS PUTUSAN PENGADILAN NEGERI MAKASAR NOMOR 518/PID.SUS/2019/PN.MKS). - Muhammad Reyhan Ramadhani (2022)
The punishment of online fraud perpetrators is based on the criminal justice system that applies in Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE), where in reality the punishment is the application of criminal sanctions that cannot be separated from justice judged by the panel of judges in online fraud cases. . Therefore, the problems in this study include: 1. How is the application of alternative and inclusion charges according to the Criminal Code (KUHP)? 2. What is the judge's consideration in the decision on the decision Makassar District Court in the context of law enforcement against online fraud perpetrators who harm the community? The theory used in this study is based on the use of criminal justice theory, cyber crime theory, law enforcement theory, and justice theory. While the research method used is normative legal research, with data collection techniques in the form of literature and legislation studies, qualitative data analysis techniques. The results of the study conclude that: 1. The application of alternative charges and inclusion according to the Criminal Code (KUHP) has complied with the applicable laws and regulations. 2. Based on the consideration of the Makassar District Court Judge's Decision, the panel of judges chose the second alternative indictment because they considered the defendant to be the one who forced other people to do it or the agent (Doenpleger).